Using National Artistic Traditions to Enhance Students’ Visual Arts Competencies - Ataullayeva E’zoza Mansur qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the pedagogical potential of incorporating national artistic traditions in visual arts lessons. Drawing on the research of Shovdirov S.A., it emphasizes the role of traditional motifs, patterns, and cultural art forms in developing students’ artistic literacy, creative thinking, and aesthetic sensitivity. The study highlights interactive approaches, practical exercises, and project-based learning as effective strategies to integrate national heritage into contemporary art education.